Two tautomers in the same crystal: 3-(4-fluorophenyl)-1H-pyrazole and 5-(4-fluorophenyl)-1H-pyrazole - Thammarse S. Yamuna; Manpreet Kaur; Jerry P. Jasinski; Brian J. Anderson; H. S. Yathirajan (Acta Crystallographica Section E, 2014)
The title co-crystal, 3-(4-fluorophenyl)-1H-pyrazole–5-(4-fluorophenyl)-1H-pyrazole (1/1), C9H7FN2, crystallizes with four independent molecules (A, B, C and D) in the asymmetric unit exhibiting two tautomeric forms (A and D; B and C) due to N—H proton exchange between the two N atoms of the pyrazole ring. The dihedral angles between the mean planes of the pyrazole and benzene rings are 15.6 (1), 19.8 (9), 14.0 (1) and 10.7 (7)° in molecules A, B, C and D, respectively. In the crystal, N—H...N hydrogen bonds link the four molecules in the asymmetric unit into a ring with an R44(12) motif. Furthermore, weak C—H...F interactions link the molecules into a three-dimensional network.